2023
DOI: 10.1186/s12974-023-02822-w
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-5 inhibition improves neural regeneration in experimental autoimmune neuritis

Felix Kohle,
Robin Ackfeld,
Franziska Hommen
et al.

Abstract: Background Autoimmune neuropathies can result in long-term disability and incomplete recovery, despite adequate first-line therapy. Kinesin-5 inhibition was shown to accelerate neurite outgrowth in different preclinical studies. Here, we evaluated the potential neuro-regenerative effects of the small molecule kinesin-5 inhibitor monastrol in a rodent model of acute autoimmune neuropathies, experimental autoimmune neuritis. Methods Experimental auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…However, the investigated therapies themselves are not feasible treatment options due to supraphysiological required doses ranging from 40-300 mg/kg [8, 10,34,35], in some cases twice a day dosing [8,9]. Further, many compounds exhibit off target effects and toxicity [7,10,11,27]. While some examples, such as sphingosine-1-phosphate inhibitors [27] or peroxisome proliferator-activated receptor gamma (PPARγ) antagonists [36], act systemically on immune organs and circulating immune cells, several examples act on sites within affected nerves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the investigated therapies themselves are not feasible treatment options due to supraphysiological required doses ranging from 40-300 mg/kg [8, 10,34,35], in some cases twice a day dosing [8,9]. Further, many compounds exhibit off target effects and toxicity [7,10,11,27]. While some examples, such as sphingosine-1-phosphate inhibitors [27] or peroxisome proliferator-activated receptor gamma (PPARγ) antagonists [36], act systemically on immune organs and circulating immune cells, several examples act on sites within affected nerves.…”
Section: Discussionmentioning
confidence: 99%
“…The non-nitrogen containing bisphosphonate, clodronate, was shown to eliminate nerve macrophages and attenuate EAN when administered therapeutically after symptom onset [6]. The kinesin-5 inhibitor monastrol reduced EAN by enhancing neurite outgrowth within axons [7]. Importantly, this therapy was administered at peak of disease, which re ects the time when most patients are diagnosed with EAN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are no currently available clinical trials for monastrol specifically (Kohle et al, 2023), other HsEg5 inhibitors, such as ispinesib and quinazoline ring-containing compounds have entered clinical trials (Zhang et al, 2005). However, these inhibitors have shown little clinical success.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…It was found that Eg5 inhibition in the human xenograft models, causes cell death and demonstrates anti-cancer activity [ 7 ]. Eg5 inhibitors are characterised by their selectivity and safety, because Eg5 functions only during mitosis; and does not affect the non-proliferative cells, which renders Eg5 inhibitors as selective inhibitors [ 8 ]. In addition, Eg5 does not induce neuropathic side effects, which are found with microtubules inhibitors, due to the absence of the Eg5 protein in the adult peripheral nervous system [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%